2020
DOI: 10.1186/s12913-020-05965-1
|View full text |Cite
|
Sign up to set email alerts
|

Health status, care needs, and assessment for beneficiaries with or without dementia in a public long-term care insurance pilot in Guangzhou, China

Abstract: Background Chinese government launched a pilot study on public long-term care insurance (LTCI) recently. Guangzhou is one of the fifteen pilot cities, officially started providing LTCI in August 2017. An in-depth analysis of experimental data from the pilot city may provide suggestions for developing a fair and effective LTCI system. This study aimed to evaluate the LTCI pilot by exploring the characteristics and care needs of claimants, and performance of the assessment tool. Methods A retrospective cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…People familiar with the hospital consultation process could provide services for the elderly with the stable condition and self-care abilities; nursing students and interns, a group with certain medical professional knowledge after training, could accompany the elderly with the stable condition and semi-disabled to the consultation; the elderly with more semidisabled and disabled with the serious condition could be accompanied by nurse practitioners with clinical work experience. Hence, a comprehensive assessment and grading system is required, together with needs-led EMES [32].…”
Section: Discussionmentioning
confidence: 99%
“…People familiar with the hospital consultation process could provide services for the elderly with the stable condition and self-care abilities; nursing students and interns, a group with certain medical professional knowledge after training, could accompany the elderly with the stable condition and semi-disabled to the consultation; the elderly with more semidisabled and disabled with the serious condition could be accompanied by nurse practitioners with clinical work experience. Hence, a comprehensive assessment and grading system is required, together with needs-led EMES [32].…”
Section: Discussionmentioning
confidence: 99%
“…Of the few studies to uncover barriers to accessing LTCI in Guangzhou, Wu et al (2020) found that people with dementia failed to apply for LTCI benefits because the need assessment tool, that is, the Barthel index, did not assess claimants' cognitive impairments. Additionally, Zhang et al (2021) suggested that permitting people to control and direct services and providing more information and support might increase service utilization in Guangzhou.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Retired people, people who had not made prior contributions to LTCI, and people suffering long-term functional disabilities (six months or more), can receive LTCI benefits if they previously had medical insurance. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, public LTCI may have protective effects on health, particularly for vulnerable individuals (such as those with chronic conditions) as the policy aims for inclusivity and social effectiveness by offering basic care provision and longer-term services and supports. 11 …”
Section: Introductionmentioning
confidence: 99%